IC 6539 Tourmaline - I. AITKENS (The National Institute for Occupational Safety and Health (NIOSH), 1931)
Tourmalines are among the most beautiful of all the semiprecious stones, and are unsurpassed even by corundum in variety of hue. The stones most suited to jewelry purposes are those comparatively free from iron. One reason for the fact that the tourmaline has advanced rapidly in public favor in this country is that it is found in California in great profusion and of extraordinary quality. The superb green and especially the pink crystals found at Pala and Mesa Grande in San Diego County, Calif., are deemed superior to tourmalines from all other localities.